Tectonostratigraphic significance of the Neogene sedimentary record of northwestern Austral-Magallanes Basin, Argentinean Patagonia (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Despite their geodynamic significance, the stratigraphy and paleoenvironments of the lower-middle Miocene clastic deposits, genetically related to subduction-driven lithospheric processes at the latitude of the Chile Triple Junction are poorly known. These beds, outcropping along the foothills of the Southern Patagonian Andes in the northwestern edge of the Austral-Magallanes Basin, include the marine Centinela Formation transitionally covered by the continental Río Zeballos Group. The aim of this work is to present an integrated stratigraphic section and to discuss its paleoenvironmental evolution, based on facies analysis. We inquired into possible tectonic-drivers during continentalization including a short extensional episode affecting the basal Miocene sequences associated to the initial stages of the Andean uplift. We measured a 980 m-thick succession, subdivided into three sedimentary units (SU I, SU II and SU III). The lower SU I is dominated by shallow marine, bioturbated sandstones and heterolithic deposits. SU II is dominated by interbedded medium- to pebbly-grained cross-stratified sandstones and mudstones, interpreted as fluvial channels and floodplains with incipient paleosols. Following, SU II shows a clear upward increase in the sandstone/mudstone ratio. Topping the sequences, SU III is composed of structurless and cross-bedded conglomerates interbedded with coarse-grained sandstones, interpreted as channel and sheet-flood deposits within an alluvial fan. The whole coarsening upward trend, from shallow marine to fluvial and finally to alluvial fan deposits, suggests that these deposits were influenced by a progressive reduction in accommodation space. The sequence is covered by basalts, truncated by a regional relictic surface composed of terrace conglomerates of the Rodados Patagónicos , reflecting basin abandonment and generation of a bypass surface during the late Miocene-Quaternary. Based on our results, published U-Pb detrital ages, and thermochronological data, we relate the evolution of the Neogene sedimentary systems to a synchronous contraction-related eastward migration of the deformation front of the adjacent Andean orogenic belt, followed by neutral tectonics.